Prevalence of Five-Child-Killer Diseases and Under-Five Mortality in Adamawa State, Nigeria - Nafiu, Lukman Abiodun; Hamidu, Umaru Waniyos (NIU Journal of Social Sciences; Vol 3 No 1 (2017): KIU Journal of Social Sciences, Vol. 3 No. 1, March 2017, 2017)
This study investigates the prevalence of the five-child killer diseases and its cause effect on under-five mortality. It uses an entirely quantitative approach with secondary data between 2001 and 2015 obtained from the data bank of Adamawa State Primary Health Care Development Agency (PHCDA). Data was collected regarding the number of children immunized and number of children that were infected but later died due to Pneumonia, Diarrhoea, Measles, Tetanus, Polio and the overall under-five mortality irrespective of diseases within that time frame. The study measures prevalence rate per a thousand live birth and uses Newey-West regression tool for analysing and developing a model. The results indicate that the prevalence rates have generally been decreasing with Pneumonia recording the highest prevalence and Tetanus recording the lowest prevalence. Polio was excluded from the analysis because it did not register any incidences or deaths. The regression model shows that there is a strong positive and significant relationship between Pneumonia and under-five mortality. The model also shows a weak positive and non-significant relationship between diarrhoea and under-five mortality. Furthermore, there was a strong positive but non-significant relationship between measles and under-five mortality and a negative non-significant relationship between tetanus and under-five mortality. The child killer diseases explained 60.92 percent cause effect on overall under-five mortality and the model is statistically significant. The study recommends that government needs to implement the Global Action Plan for Pneumonia and Diarrhoea (GAPPD) as campaigned by WHO and UNICEF, adequate nutrition should be given to these children and children infected with HIV/AIDs should be given daily vaccines to reduce the risk of contracting these five-child-killer-diseases. Keywords: Five-child killer diseases, prevalence, nutrition, mortality and under-five children.